(untitled) (Global Journals of Research in Engineering, 2013)
Metal bellows is a precision component that is welded along the peripheries of both inside and outside diameters. A development of computer aided design program for the three kinds of welded metal bellows has been studied by Auto LISP language of AutoCAD in this thesis. In this study, this program is sequentially constructed dialog boxes, with which the expected shape of the metal bellows would be obtained quickly and exactly by input of the basic data that the initial radius, inner and outer diameters, pitch, thickness of plate and land length is given. The effects on stress distribution of the bellows can be estimated using a commercial FEM code of ANSYS Workbench when altering some design variables. As a result, this program studied in this paper revealed the advantages as follows, users can obtain the shape of the bellows more easily by input the variables or adding more information, moreover, this program can be revised simply by changing the variables according to the demands in industry and the drawing of metal bellows can be connected to other CAD programs for modeling and FEM analysis